A Qualitative Exploration of Burnout and Self-Care Among Novice Psychotherapists - Masengo, Lydie (Université d'Ottawa / University of Ottawa, 2022)
A gap exists in the literature exploring the burnout and self-care experiences of novice psychotherapists, despite their greater susceptibility to burnout. The aim of the present study was to begin filling the gap by exploring the lived experiences of burnout among novice psychotherapists and the self-care strategies they employed to combat burnout. Three research questions guided this exploration: (1) How do novice psychotherapists experience burnout? (2) What strategies do novice psychotherapists use to overcome their burnout? (3) How has novice psychotherapists’ self-care strategies changed as a result of experiencing burnout? Four novice psychotherapists were interviewed using a semi-structured interview protocol to gain an insight into their experiences. Using an inductive approach to Thematic Analysis, six main themes, thirteen categories and twenty-eight codes emerged. The six themes were the following: (1) The experience of burnout, which was divided into three categories and included nine codes (2) The strategies employed to combat burnout, which was divided into two categories and included seven codes (3) The meaning of self-care, which was divided into two categories and included three codes (4) Ethical considerations, which was divided into three categories and included three codes (5) Recommendations, which was divided into two categories and included five codes and (6) Looking ahead, which was divided into one category and included one code. Burnout is a debilitating experience that impact personal life, client care, and society. Discussion includes implications for novice psychotherapists, pedagogy and practice, and society.
Keywords: burnout; self-care; novice psychotherapists; client care; pedagogy